บรรยากาศการพัฒนาทรัพยากรมนุษย์ พันธะสัญญาทางใจในงานและพฤติกรรมการเป็นสมาชิกที่ดีขององค์การของบุคลากรสายสนับสนุน มหาวิทยาลัยสงขลานครินทร์ - นฤบาล ยมะคุปต์ (มหาวิทยาลัยสงขลานครินทร์, 2024)
This institute research study the effect of human resource development climate (HRDC) and work engagement toward organizational citizenship behavior in the context of supporting staffs of Prince of Songkla university. It is a quantitative research study using both offline and online questionnaires. A total of 370 subjects was derived using Krejcie and Morgan's sample size formula. The data analysis is based on Partial Least Square Structural Equation Modeling (PLS-SEM). The results demonstrated moderate level of human resource development climate and high level of work engagement and organizational citizenship behavior perceived by supporting staffs. Human resource development climate and work engagement influenced the organizational citizenship behavior with an explanation power of 30.90% (Coefficient of Determination: R2 =.309), that is, at a 99% confidence level, human resource development climate influenced the organizational citizenship behavior (B= .389, t=12.075, p=.000) and work engagement influenced the organizational citizenship behavior (B= .209,t=4.509, p=.000).